ANTIBODIES AGAINST BOVINE VIRAL DIARRHEA VIRUS AND ITS ASSOCIATION WITH REPRODUCTIVE PROBLEMS IN EWES OF THE CENTRAL SIERRA OF PERU - Flores B., Daniel (2010)
The aim of the Case-Control study was to determine the association between bovine viral diarrhea virus (BVDV) and reproductive failure in ewes from a commercial farm in the Central Sierra of Peru. Four hundred and forty ewes from two farm locations were randomly selected into two groups: the Case group (n=220) included barren and aborting ewes, and the Control group formed by ewes without reproductive failures. Blood samples were collected from both groups for testing antibodies against BVDV by the neutralization test. The 69.5 ± 4.4% (306/440) of ewes of both groups had antibodies against BVDV, while 73.6% (162/220) of seropositive ewes were from the Case group and 65.5% (144/ 220) were from the Control group. None statistical association between seropositive ewes and reproductive failures was found. Antibody titers against BVDV in both groups ranged from 2 to >256. The results indicate that BVDV is widely distributed in the sheep population but its role in the reproductive failures could not be determined.